From Depeasantization to Repeasantization: Farmer’s Struggle to Revive Agriculture Following the Construction of YIA Airport - Farah Qurrota Ayuni; Agung Wicaksono (PT Publikasiku Academic Solution, 2026)
The construction of Yogyakarta International Airport (YIA), which involved the conversion of farmland into non-agricultural and industrial land, has led to depeasantization. One of the groups most significantly affected is the peasants in Glagah Village. However, peasants are also actors with agency; they respond to change and struggle for autonomy over agrarian production. The peasants’ struggle for autonomy is referred to as repeasantization. This study aims to identify how peasants in Glagah Village struggle for autonomy and territory, and to explain the processes of depeasantization and repeasantization occurring in Glagah Village. The research was conducted in Glagah Village, and the methods used were non-participant observation, semi-structured interviews, and literature studies. A total of six informants from four households were involved, consisting of both peasants and ex-peasants. The results show that depeasantization occurs due to the loss of peasant autonomy and territory, characterized by farmland loss, a decrease in the number of peasants, and changes in agrarian dynamics. In response to depeasantization, peasants struggle for autonomy by practicing sharecropping and building solidarity among peasants by lending farmer cards to one another for purchasing fertilizer.